1997
DOI: 10.1074/jbc.272.18.11812
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Protein Kinase from Dictyosteliumwith Homology to the Novel Catalytic Domain of Myosin Heavy Chain Kinase A

Abstract: Myosin II assembly and localization into the cytoskeleton is regulated by heavy chain phosphorylation in Dictyostelium. The enzyme myosin heavy chain kinase A (MHCK A) has been shown previously to drive myosin filament disassembly in vitro and in vivo. MHCK A is noteworthy in that its catalytic domain is unrelated to the conventional families of eukaryotic protein kinases. We report here the cloning and initial biochemical characterization of another kinase from Dictyostelium that is related to MHCK A. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…The D. discoideum genome data base was searched using MHCK B catalytic domain sequence (Clancy et al, 1997), and as a result, a DNA sequence (contig 4260) carrying a similar catalytic domain sequence was identified. The open reading frame (ORF) of the new gene was predicted using the DNAStar software package, and primers were designed for PCR amplification of full-length cDNA.…”
Section: Cloning Of Vwka Cdnamentioning
confidence: 99%
See 2 more Smart Citations
“…The D. discoideum genome data base was searched using MHCK B catalytic domain sequence (Clancy et al, 1997), and as a result, a DNA sequence (contig 4260) carrying a similar catalytic domain sequence was identified. The open reading frame (ORF) of the new gene was predicted using the DNAStar software package, and primers were designed for PCR amplification of full-length cDNA.…”
Section: Cloning Of Vwka Cdnamentioning
confidence: 99%
“…Molecular cloning and biochemical characterization studies demonstrated that at least three Dictyostelium ␣-kinases genes encode enzymes that can specifically phosphorylate myosin II heavy chain (MHC) in vitro and in vivo, and were thus named as MHC kinase A (MHCK A), MHC kinase B (MHCK B) and MHC kinase C (MHCK C) (Futey et al, 1995;Clancy et al, 1997;Luo et al, 2001;Liang et al, 2002;Rico and Egelhoff, 2003). Although there are many open questions regarding the upstream regulation of Dictyostelium MHCKs, it is generally established that these enzymes play a direct role in myosin II phosphorylation and regulation of myosin II assembly dynamics in this organism (de la Roche et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A structurally related kinase, MHCK B, has been identified and cloned from Dictyostelium via sequence homology to the catalytic domain of MHCK A. Although native MHCK B has not yet been purified, a bacterially expressed truncation of MHCK B phosphorylates MHC preferentially at the mapped regulatory sites discussed above (16). Another Dictyostelium homologue of MHCK A that has been identified by cDNA and genomic sequencing has been named MHCK C, although it has not yet been characterized at the protein level (GenBank TM accession number AF079447).…”
mentioning
confidence: 99%
“…Despite their number and essential roles in a number of events, only a few CaMBPs have been characterized fully in Dictyostelium. Myosin heavy chain kinase, a Ca 2ϩ /CaM-dependent enzyme involved in myosin assembly, has been shown to be integral in cell motility (27,28). Myosin I isoforms are Ca 2ϩ -independent CaM targets (17).…”
mentioning
confidence: 99%